2000
DOI: 10.1017/s0007114500001926
|View full text |Cite
|
Sign up to set email alerts
|

The role of meat in the expression of rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is characterized by inflammation of the synovial tissues in the joints. A number of papers related to dietary components that are associated with this inflammation are reviewed. In addition, the ecological approach is used to study the links between diet and RA. Multi-country data for prevalence of RA for females from eight and fifteen countries were compared statistically with components of national dietary supply. Fat from meat and offal for the period 2 years before the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 50 publications
2
41
0
1
Order By: Relevance
“…It is also appealing from a computational perspective as it enables the use of conditional MCMC algorithms, such as the Gibbs sampler, and hence eliminates the need for computationally expensive matrix inversion. Unfortunately, however, the conditional specification given by (14) does not yield a proper joint distribution for U (i.e. one that integrates to some finite value), since the induced precision matrix is not positive definite.…”
Section: Specification Of Spatial Structurementioning
confidence: 99%
“…It is also appealing from a computational perspective as it enables the use of conditional MCMC algorithms, such as the Gibbs sampler, and hence eliminates the need for computationally expensive matrix inversion. Unfortunately, however, the conditional specification given by (14) does not yield a proper joint distribution for U (i.e. one that integrates to some finite value), since the induced precision matrix is not positive definite.…”
Section: Specification Of Spatial Structurementioning
confidence: 99%
“…Historically, diet has received considerable attention as a potential risk factor. Although studies have suggested associations, mainly regarding fruit, vegetables, meat and disease development, the results have been inconclusive [4][5][6][7][8][9][10]. Regarding the consumption of alcohol, recently published meta-analyses concluded that moderate consumption of alcohol intake is inversely associated with the development of RA [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low-protein diets may improve RA symptoms [10-13]. In ecologic studies, the prevalence of RA is higher in countries with greater consumption of red meat [14]. More recently, Pattison and colleagues [15] reported the first prospective investigation of red meat and risk for inflammatory polyarthritis (IP) and concluded that higher intakes of both red meat and protein increased the risk for IP, whereas iron – another nutrient component of meat – exhibited no association.…”
Section: Introductionmentioning
confidence: 99%